The Coal Industry. - Kernot, Charles (International Trade Ser., 2000)
The coal industry is the first publication to provide a comprehensive overview of the structure and workings of the international coal trade at the beginning of the 21st century, from exploration through to end-uses. It will be essential reading for all those involved in or new to the industry and for the financial advisory, analytical and investment community internationally.